Dampak Krisis Keuangan Global 2008 terhadap Volatilisas Return Saham Perbankan di BEI - Taftazani, Afif M.; Irwanto, Abdul Kohar; Cahyadi, Eko Rudy (Jurnal Aplikasi Manajemen, 2015)
The study aims to analyze and create the model of stock returns movement in a banking company in IDX and make test for asymmetric effects in stock returns volatility due to the global financial crisis in 2008. Volatility is generally characterized by the rise and fall of a value at specified intervals with high deviation. As a result, the volatility causes an unstable condition, varied and hard to predict. Moreover, High volatility impacts an inconstant of variance and error, causing heterocedastity effects. The existence of an extraordinary event that causes a shock can influence volatility affecting an asymmetric of variance and error, commonly called asymmetric shock/effect. This shock is due to the global financial crisis of 2008. This research is an event study, where the event being analyzed as the impact of the global crisis of 2008. The Study in which relate to the effect of a crisis on stock return volatility in Indonesia is still rare. It is expected to help of the research and provide feedback to another researchers in order to study and develop the studies with similar themes, especially concerning to the impact/influence of the crisis or the influence of others. For investors, it can be used as a consideration of the investment decision making more accurate. The data that has been analyzed are daily stock price period August 8, 2006 to 29 August 2014 at five banking companies: BMRI, BBNI. BBKP, BII and BLNI.